2006
DOI: 10.1016/j.neuroscience.2006.08.030
|View full text |Cite
|
Sign up to set email alerts
|

Neuronal correlates of signal detection in the posterior parietal cortex of rats performing a sustained attention task

Abstract: The posterior parietal cortex (PPC) plays an integral role in visuospatial attention. Evidence suggests that neuronal activity in the PPC predicts the allocation of attention to stimuli. The present experiment tested the hypothesis that in rats performing a sustained attention task, the detection of signals, as opposed to missed signals, is associated with increased PPC unit activity. Single unit activity was recorded from the PPC of rats and analyzed individually and as a population vector for each recording … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
27
3

Year Published

2007
2007
2017
2017

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(34 citation statements)
references
References 72 publications
4
27
3
Order By: Relevance
“…Other studies have shown that PPC neurons respond to target, but not task-irrelevant, stimuli (Broussard et al, 2006), whereas PFC neurons respond to target and distractor stimuli (Gill et al, 2000). A critical methodological difference may account for the discrepancy between previous work and our finding.…”
contrasting
confidence: 99%
See 1 more Smart Citation
“…Other studies have shown that PPC neurons respond to target, but not task-irrelevant, stimuli (Broussard et al, 2006), whereas PFC neurons respond to target and distractor stimuli (Gill et al, 2000). A critical methodological difference may account for the discrepancy between previous work and our finding.…”
contrasting
confidence: 99%
“…In the previous study, recordings were made after the rats were repeatedly exposed to the distractor. Repeated exposure to a distractor produces performance of ϳ70% accuracy in detecting signals in the presence a 0.5 Hz flashing house light (Gill et al, 2000;Broussard et al, 2006). In contrast, our Sham-LX subjects accurately detected 40% of signals during the flashing house-light session.…”
mentioning
confidence: 65%
“…These are all regions that have been implicated in visuospatial functions (Vaudano et al, 1991;Shi and Cassell, 1997;Broussard et al, 2006). The pattern of subcortical connections of the POR also supports a strong bias towards visual information processing.…”
Section: Discussionmentioning
confidence: 64%
“…In Mongolian gerbils, isolation rearing reduces the axonal projections from the mPFC to the parietal cortex (Bagorda, Teuchert-Noodt, & Lehmann, 2006). It has been known that the parietal cortex in humans is involved in the modulation of spatial attention by fear-conditioned stimuli (Armony & Dolan, 2002), and the parietal cortex in rats is involved in maintaining selective attention to signals (Broussard, Sarter, & Givens, 2006;Corwin & Reep, 1998). Although it is still unclear whether isolation rearing in rats causes dysconnection between the mPFC and the parietal cortex, and even neural damage to the parietal cortex, in future studies it will be important to address whether multimodal parietal regions of rats, such as the posterior parietal cortex, contribute to the precedence-effect-induced enhancement of PPI.…”
Section: Discussionmentioning
confidence: 99%